Facets of Combinatorial Optimization: Festschrift for Martin Grötschel - Jünger, Michael; Reinelt, Gerhard (SpringerLink Bücher, 2013)
Martin Grötschel - a tribute: M.Jünger and G.Reinelt.- Facets and rank of integer polyhedra: M.Padberg.- Constructing extended formulations from reflection relations: V.Kaibel and K.Pashkovich -- Exact algorithms for combinatorial optimization problems with submodular objective functions: F.Baumann, S.Berckey, and C.Buchheim -- Solving k-way graph partitioning problems to optimality: The impact of semidefinite relaxations and the bundle method: M.F. Anjos, B.Ghaddar, L.Hupp, F.Liers and A.Wiegele -- Mirror-descent methods in mixed-integer convex optimization: M.Baes, T.Oertel, Ch.Wagner and R.Weismantel -- On perspective functions and vanishing constraints in mixed-integer nonlinear optimal control: M.Jung, Ch.Kirches, and S.Sager -- Beyond perfection: computational results for superclasses: A.Pecher and A.Wagler -- Algorithms for junctions in acyclic graphs: C.E. Ferreira and A.J.P. Franco -- A primal heuristic for nonsmooth mixed integer nonlinear optimization: M.Schmidt, M.C. Steinbach, and B.M. Willert -- Flow-Over-Flow Models and an Application to the Scheduling and Routing of Fly-in Safari Planes: A.Fügenschuh, G.Nemhauser, and Y.Zeng -- How Many Steiner Terminals Can You Connect in 20 Years?: R.Borndörfer, N -- D.Hoang, M.Karbstein, Th.Koch, and A.Martin -- Robust heaviest connected subgraphs in networks: E.Alvarez Miranda, I.Ljubic, and P.Mutzel.- Algorithms for scheduling sensors to maximize coverage time: R.da Ponte Barbosa and Y.Wakabayashi -- From vertex-telecenters to subtree-telecenters: Z.Win and C.Kyi Than -- A new algorithm for MINLP applied to gas transport energy cost minimization: B.Geißler, A.Morsi and L.Schewe -- Progress in academic computational integer programming: Th.Koch, A.Martin, and M.E. Pfetsch -- Mixed Integer Programming: Analyzing 12 Years of Progress: T.Achterberg and R.Wunderling .